Evaluating agricultural extension and education projects: the VELVET approach. Issue 4 (18th May 2020) - Charatsari, Chrysanthi; Lioutas, Evagelos D.
ABSTRACT: This practical note presents an alternative, learner-centred model for the evaluation of agricultural extension and/or education projects. The VELVET model is based on six evaluation axes: values, expectations, learning, value change, empowerment, and transformation. Using the identification of farmers' value systems and the determination of their expectations as a jumping-off point for the evaluation of a project, VELVET assesses the learning achieved over the course of an extension/education project, the degree to which participation in the project leads to a change of trainees' value systems, and the project's contribution to participants' empowerment and transformation.